Left atrial appendage occlusion in patients with atrial fibrillation and large prevalence of prior intracranial bleeding. Issue 8 (August 2020) - Barocelli, Federico; Coli, Stefano; Crocamo, Antonio; Guidorossi, Angela; Cattabiani, Maria A.; Preti, Francesca; Bosi, Davide; Spaziani, Cristina; Lina, Daniela; Menozzi, Alberto; Solinas, Emilia; Pelà, Giovanna; et al.
Abstract : Background: Left atrial appendage occlusion (LAAO) represents an alternative approach for the prevention of cardioembolic stroke in patients with nonvalvular atrial fibrillation (NVAF) and contraindication for oral anticoagulation (OAC). The aim of our study was to analyse the outcomes in patients treated with LAAO, with a focus on cases with previous intracranial bleeding. Methods: Sixty patients with NVAF underwent LAAO (75.4 ± 9 years); mean CHA2 DS2 -VASc was 4.4 ± 1.7, mean HAS-BLED 3.2 ± 0.9. Thirty-two patients (53.3%) reported previous intracranial bleeding. Ischaemic and bleeding events recorded during follow-up were compared with expected event rates according to CHA2 DS2 -VASc and HAS-BLED scores. Results: Device implantation was successful in 58 patients (96.7%). The antiplatelet therapy was tailored according to patients' bleeding risk. During follow-up (2.32 ± 1.5 years) 3 ischaemic strokes and 1 transient ischaemic attack occurred, versus 13 total expected thromboembolic events ( P  = 0.033); 5 major bleedings were observed, versus 7 expected ones, if the patients were under OAC. Considering the combined endpoint (thromboembolic and major bleeding events) 9 events were observed versus 20 expected major events ( P  = 0.031). In the prespecified subgroup of patients with previous intracranial bleeding, two ischaemic strokes and one transient ischaemic attack were observed during follow-up versus six total expected thromboembolic events; no intracranial bleeding recurrence was recorded. Regarding the combined endpoint four major events were recorded versus nine expected ones. Conclusion: LAAO is an efficient and safe option for the prevention of cardioembolic stroke in patients with NVAF, high thromboembolic risk and contraindication to OAC, particularly in patients with previous intracranial bleeding.